Effect of Prostaglandin I2 Analogs on Macrophage Inflammatory Protein 1α in Human Monocytes via I Prostanoid Receptor and Cyclic Adenosine Monophosphate. (February 2014) - Tsai, Ming-Kai; Hsieh, Chong-Chao; Kuo, Hsuan-Fu; Yang, San-Nan; Kuo, Chang-Hung; Huang, Ming-Yii; Tsai, Ying-Ming; Lee, Min-Sheng; Hung, Chih-Hsing
Aims: Inflammation plays critical roles in atherosclerosis. Chemokines are responsible for leukocyte trafficking and involve in inflammatory diseases. Macrophage inflammatory protein 1α (MIP-1α) has been implicated in atherosclerotic lesion formation. Prostaglandin I2 (PGI2 ) analog, used in pulmonary hypertension, has been reported to have anti-inflammatory functions. However, little is known about its role in the MIP-1α production in human monocytes. Methods: We investigated the effects of 3 conventional (iloprost, beraprost, and treprostinil) and 1 new (ONO-1301) PGI2 analogs, on the expression of MIP-1α expression in human monocytes. Human primary monocytes from control subjects and THP-1 cell line were treated with PGI2 analogs, with or without lipopolysaccharide (LPS) stimulation. Supernatants were harvested to measure MIP-1α levels by enzyme-linked immunosorbent assay. To explore which receptors involved the effects of PGI2 analogs on the expression of MIP-1α expression, I prostanoid (IP) and E prostanoid, peroxisome proliferator-activated receptor (PPAR)-α, and PPAR-r receptor antagonists were used to pretreat THP-1 cells. Forskolin, a cyclic adenosine monophosphate (cAMP) activator, was also used to further confirm the cAMP involvement on the effect of PGI2 analogs in MIP-1α production. Results: Three PGI2 analogs could suppress LPS-induced MIP-1α production in THP-1 cells and human primary monocytes. ONO-1301 had a similar effect. CAY 10449, an IP receptor antagonist, could reverse the suppressive effects on MIP-1α production of iloprost. Forskolin, a cAMP activator, also suppressed MIP-1α production in THP-1 cells. Conclusions: Prostaglandin I2 analogs suppressed LPS-induced MIP-1α production in human monocytes via the IP receptor and cAMP pathway. The PGI2 analog may be potential in the treatment for atherosclerosis.